Jerzy Ronard Bujański i jego twórczość (w świetle artystycznego archiwum ze zbiorów Biblioteki Śląskiej) (PDF 4,41 MB) (Książnica Śląska, 2025)
The article recalls the figure of Jerzy Ronard Bujański, an actor, director, radioman and writer. The text describes materials from his legacy, collected in the Special Collections of the Silesian Library inKatowice. The Bujański’s artistic archive contains interesting materials: his typescripts, including theatrical studies, memoirs, scenicworks (dramas, opera and ballet librettos), radio and literary texts(both prose and poetry). The author of the article characterizes thepreviously unknown work of Bujański and discusses it in terms ofthemes, problems and genres. This article supplements the biography of Jerzy Ronard Bujański and provides information about hisunknown and unprinted texts and works.